Analisis Perilaku Etik Dengan Caring Pada Perawat Di Rumah Sakit Wilayah Kabupaten Bandung - Situmorang, Roganda; Rifai, Susan; Anri; Situmorang, Elisa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: The largest healthcare workforce (nurses) has a significant impact on efforts to maintain and improve the quality of healthcare services. Nurses' behavior in providing services impacts healthcare services. Information suggests that there are still complaints about nurses' ethical behavior and caring attitudes toward patients. The purpose of this study was to analyze ethical behavior and caring among nurses in hospitals in Bandung Regency. Method: Quantitative research method, descriptive correlation type, cross-sectional approach. The population was 369 nurses, the sample calculation was determined using the Lameshaw formula of 44 nurses selected by stratified random sampling. Data collection (primary) used the distribution of nurse ethical behavior questionnaires (Cronbach Alpha value 0.996) and nurse caring questionnaires (Cronbach Alpha value 0.981). The research data used univariate analysis (frequency distribution calculation) and bivariate analysis using chi-square. Results: The majority (63.6%) of nurses exhibited poor ethical behavior, while nearly half (34.4%) exhibited moderately good ethical behavior. Most (63.6%) of nurses exhibited moderately good caring behavior, while a small proportion (20.5%) exhibited poor caring behavior. There was a significant relationship (p-value 0.000) between ethical behavior and caring behavior in nurses. The better the ethical behavior of nurses, the better their caring behavior. Conclusion: It is crucial for hospitals and nursing institutions to create a conducive work environment that supports the implementation of ethics, inseparable from caring behavior. Training for nurses is needed to improve understanding of ethical and caring behavior in daily practice, as well as further research to explore effective strategies for enhancing ethical and caring behavior in nurses to improve service quality as a culture of nursing care.